Marcadores prosódicos da escrita literária: uma análise da obra Manuelzão e Miguilim, de Guimarães Rosa - Esparsa, Michel Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
to each other. These approaches reveal the speaker's attitudes, their feelings expressed in statements and in the contexts in which those expressions are used. Cagliari (1989) calls this kind of discursive reference as prosodic markers in literary writing. In this project, the corpus for the analysis comes from the work of Guimarães Rosa: Manuelzão e Miguilim. The main goal of the present project is to develop studies on the subject, since there is virtually nothing done about the prosodic writing markers. Develop working methods is an important objective, in order to show how the prosodic markers can be studied. This type of study is not only important to linguistics: phonetics, textual analysis and discourse, but also to literary studies. Different ages of literary expressions used differently such resources as shown by the work of Cagliari (1989). The methodology of this project starts collecting data to compose the corpus with examples categorized as prosodic markers. Then, according to prosodic theories, these expressions are classified in types. The contexts in which they appear are important elements and they will be highlighted. The narrative of the plot is also an important context. Dialogues are good source of prosodic markers. In the work of Guimarães Rosa: Manuelzão e Miguilim, it was observed that the author likes to reveal the feelings of the characters in the novel through stated words in their speech. There are prosodic markers showing feeling like: intimidating, serene, gentle, cheerful, worried, angry, with irony, etc. The authors also refer to the fact that the character pronounced his speech with different voice qualities such as loud, hoarse, whispering, etc. This project studies the association between some prosodic elements of speech and their occurrence in literary texts as prosodic writing markers, as defined in the project. The data come from the phonetic descriptions of words and expressions regarded as prosodic...

personagem se endereça a outro. Essas referências dizem respeito às atitudes do falante, ao seu sentimento expresso através dos enunciados que profere e do contexto em que essas expressões são usadas. Cagliari (1989) chama esse tipo de referência discursiva de marcadores prosódicos da escrita literária. No caso do presente projeto, o material de onde será tirado o corpus para a análise é a obra de Guimarães Rosa: Manuelzão e Miguilim(1994). O principal objetivo científico é desenvolver estudos sobre o assunto, uma vez que há poucos trabalhos feito a respeito dos marcadores prosódicos da escrita. Desenvolver metodologias de trabalho é um objetivo importante, mostrando como os marcadores prosódicos podem ser estudados. Esse tipo de estudo serve não apenas à fonética, à análise textual e do discurso, mas também aos estudos literários. Diferentes épocas literárias utilizaram de forma distinta tais recursos, como mostram os trabalhos de Cagliari (1989). A metodologia do presente projeto consiste em extrair de um corpus (obra literária) os exemplos classificados como marcadores prosódicos. Em seguida, tais expressões são classificadas por tipos, de acordo com as teorias prosódicas. Os contextos em que elas aparecem constituem elementos importantes e serão destacados. A própria trama da narrativa constitui uma situação importante, um pano de fundo para os diálogos e falas com marcadores prosódicos. Observou-se na obra de Guimarães Rosa: que o autor gosta de revelar os sentimentos dos personagens por meio das falas nos diálogos. Ele usa muitos marcadores prosódicos, mostrando falas peremptórias, serenas, suaves, alegres, preocupadas, iradas, com ironia, etc., Além disso, refere-se ao fato de o personagem ter dito em voz alta, gritado, murmurando, etc. O presente projeto estuda a associação entre as descrições fonéticas da prosódia da fala e a referência de marcadores prosódicos da escrita, com especial...
Keywords: Rosa, João Guimarães 1908-1967 Manuelzão e Miguilim; Literatura - Historia e critica; Fonética; Phonetics